Neuroinflammation in Huntington’s disease: From animal models to clinical therapeutics - Jia, Qingqing; Li, Shihua; Li, Xiao-Jiang; Yin, Peng (Frontiers in Immunology, 2022)
Huntington's disease (HD) is a progressive neurodegenerative disease characterized by preferential loss of neurons in the striatum in patients, which leads to motor and cognitive impairments and death that often occurs 10-15 years after onset of symptoms. The expansion of a glutamine repeat (>36 glutamines) in the N-terminal region of huntingtin (Htt) has been defined as the cause of HD, but the mechanism underlying neuronal death remains unclear. Multiple mechanisms, including inflammation, may jointly contribute to HD pathogenesis. Altered inflammation response is evident even before the onset of classical symptoms of HD. In this review, we summarize the current evidence on immune and inflammatory changes, from HD animal models to clinical phenomenon of patients with HD. The understanding of the impact of inflammation on HD would help develop novel strategies to treat HD.